A non-local elliptic–hyperbolic system related to the short pulse equation. (January 2020) - Coclite, Giuseppe Maria; di Ruvo, Lorenzo
Abstract: In this paper, we prove the well-posedness of a non-local elliptic–hyperbolic system related to the short pulse equation. It is a model which describes the evolution of the electrical field of linearly polarized continuum spectrum pulses in optical waveguides, including fused-silica telecommunication-type or photonic-crystal fibers, as well as hollow capillaries filled with transparent gases.